Physiology and Biochemistry of Liver Dysfunction in Non-Alcoholic Fatty Liver Disease - Sobia Ali, Muhammad Zahid, Amber Zaidi, Farzana Salman, Mohammad Haroon, Arbab Muhammad Kashif Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is a liver condition that is one of the most common chronic liver diseases and has strong associations with obesity, insulin resistance, dyslipidaemia and metabolic syndrome. It is caused by abnormal accumulation of fat in the liver and can lead to steatohepatitis, fibrosis, cirrhosis and liver-related complications. Physiological changes like high BMI and central obesity, and biochemical changes like liver enzymes and lipid metabolism abnormalities, have significant impact in the progression of NAFLD. Objective: To assess the physiological and biochemical patterns of liver dysfunction among patients with non-alcoholic fatty liver disease. Methods: The study was descriptive cross sectional study which was carried out from January 2022 to January 2023 at Mohammad College of Medicine, Peshawar. The number of patients who were diagnosed with NAFLD was 72 patients, which was obtained by non-probability consecutive sampling. Age, gender, BMI, waist circumference, DM, HTN, dyslipidemia, liver function tests, FBS, HbA1c, lipid profile and the grading of fatty liver using ultrasound were documented. Analysis of data was carried out using SPSS version 25. The data obtained were presented using descriptive statistics of quantitative variables mean and standard deviation while qualitative variables were presented using frequency and percentage. Association and correlation were evaluated by suitable statistical tests and a p-value of <0.05 was considered significant. Results: The mean age of patients was 42.8 ± 10.6 years. Out of 72 patients, 41 (56.9%) were females and 31 (43.1%) were males. The mean BMI was 29.4 ± 4.1 kg/m², and obesity was present in 34 (47.2%) patients. Diabetes mellitus was found in 27 (37.5%), hypertension in 25 (34.7%), and dyslipidemia in 46 (63.9%) patients. Ultrasound grading showed Grade I fatty liver in 31 (43.1%), Grade II in 28 (38.9%), and Grade III in 13 (18.0%) patients. Mean ALT, AST, ALP, and GGT levels increased progressively with higher fatty liver grade. ALT increased from 49.2 ± 18.5 U/L in Grade I to 82.6 ± 25.7 U/L in Grade III, while GGT increased from 44.6 ± 19.8 U/L to 87.2 ± 28.6 U/L. BMI, waist circumference, triglycerides, and fasting blood glucose showed positive correlations with liver enzyme levels. Conclusion: NAFLD was commonly associated with obesity, central adiposity, dyslipidemia, impaired glucose metabolism, and elevated liver enzymes. Higher ultrasound grades of fatty liver were linked with greater biochemical liver dysfunction. Early detection of metabolic risk factors, regular biochemical monitoring, weight control, and lifestyle modification are important to prevent disease progression. Keywords: Non-alcoholic fatty liver disease, liver dysfunction, liver enzymes, obesity, dyslipidemia, insulin resistance, ultrasound grading.